The Relationship between Multicultural Education and the Democratic Political System in Indonesia : PAI's Perspective - M. Fatahuddin Al-Ansyar; St. Wardah Hanafie Das (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
This study discusses the material on the relationship between multicultural education and the democratic political system in Indonesia from the perspective of Islamic Religious Education. Multicultural education adheres to the principle of equality of rights and degrees in education, regardless of differences in ethnicity, race, religion and culture. Meanwhile, in the existing democratic political system in Indonesia, adhering to the Pancasila Democracy system which holds the principle of difference is the capital of unity, different but still one in the frame of freedom for each individual to choose the direction of democracy and politics, but does not cause division in one unit as a child of the nation. The results of this study show that there is a strong relationship between multicultural education and the democratic political system in Indonesia based on the perspective of Islamic Religious Education, the relationship is as follows: 1) Divine relationship, 2) Justice relationship, 3) Equal relationship of rights and degrees, and 4) Independence relationship.